2017
DOI: 10.1101/166785
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computational Foundations of Natural Intelligence

Abstract: New developments in AI and neuroscience are revitalizing the quest to understanding natural intelligence, offering insight about how to equip machines with human-like capabilities. This paper reviews some of the computational principles relevant for understanding natural intelligence and, ultimately, achieving strong AI. After reviewing basic principles, a variety of computational modeling approaches is discussed. Subsequently, I concentrate on the use of artificial neural networks as a framework for modeling … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 280 publications
(260 reference statements)
0
4
0
Order By: Relevance
“…Nevertheless, DNNs are of increasing interest for natural vision (Cox and Dean, 2014;Khaligh-Razavi and Kriegeskorte, 2014;Yamins et al, 2014;Güçlü and van Gerven, 2015b, a;Kriegeskorte, 2015;Cichy et al, 2016;Wen et al, 2016Wen et al, , 2017Eickenberg et al, 2017;Horikawa and Kamitani, 2017;Seeliger et al, 2017). Recent studies have shown that DNNs, especially convolutional neural networks for image recognition (Krizhevsky et al, 2012;Simonyan and Zisserman, 2014;He et al, 2016), preserve the representational geometry in object-sensitive visual areas (Khaligh-Razavi and Kriegeskorte, 2014;Yamins et al, 2014;Cichy et al, 2016), and predicts neural and fMRI responses to natural picture or video stimuli (Güçlü and van Gerven, 2015b, a;Wen et al, 2016Wen et al, , 2017Eickenberg et al, 2017;Seeliger et al, 2017), suggesting their close relevance to how the brain organizes and processes visual information (Cox and Dean, 2014;Kriegeskorte, 2015;Yamins and DiCarlo, 2016;Kietzmann et al, 2017;van Gerven, 2017). DNNs also open new opportunities for mapping the visual cortex, including the cortical hierarchy of spatial and temporal processing (Güçlü and van Gerven, 2015b, a;Cichy et al, 2016;Wen et al, 2016;Eickenberg et al, 2017), category representation and organization (Khaligh-Razavi and Kriegeskorte, 2014;Wen et al, 2017), visual-field maps (Wen et al...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, DNNs are of increasing interest for natural vision (Cox and Dean, 2014;Khaligh-Razavi and Kriegeskorte, 2014;Yamins et al, 2014;Güçlü and van Gerven, 2015b, a;Kriegeskorte, 2015;Cichy et al, 2016;Wen et al, 2016Wen et al, , 2017Eickenberg et al, 2017;Horikawa and Kamitani, 2017;Seeliger et al, 2017). Recent studies have shown that DNNs, especially convolutional neural networks for image recognition (Krizhevsky et al, 2012;Simonyan and Zisserman, 2014;He et al, 2016), preserve the representational geometry in object-sensitive visual areas (Khaligh-Razavi and Kriegeskorte, 2014;Yamins et al, 2014;Cichy et al, 2016), and predicts neural and fMRI responses to natural picture or video stimuli (Güçlü and van Gerven, 2015b, a;Wen et al, 2016Wen et al, , 2017Eickenberg et al, 2017;Seeliger et al, 2017), suggesting their close relevance to how the brain organizes and processes visual information (Cox and Dean, 2014;Kriegeskorte, 2015;Yamins and DiCarlo, 2016;Kietzmann et al, 2017;van Gerven, 2017). DNNs also open new opportunities for mapping the visual cortex, including the cortical hierarchy of spatial and temporal processing (Güçlü and van Gerven, 2015b, a;Cichy et al, 2016;Wen et al, 2016;Eickenberg et al, 2017), category representation and organization (Khaligh-Razavi and Kriegeskorte, 2014;Wen et al, 2017), visual-field maps (Wen et al...…”
Section: Discussionmentioning
confidence: 99%
“…Visual semantics explain the responses in the ventral temporal cortex but not at lower visual areas (Naselaris et al, 2009;Huth et al, 2012). On the other hand, braininspired deep neural networks (DNN) (LeCun et al, 2015), mimic the feedforward computation along the visual hierarchy (Kriegeskorte, 2015;Yamins and DiCarlo, 2016;Kietzmann et al, 2017;van Gerven, 2017), match human performance in image recognition (Krizhevsky et al, 2012;Simonyan and Zisserman, 2014;Szegedy et al, 2015;He et al, 2016), and explain cortical activity over nearly the entire visual cortex in response to natural visual stimuli (Yamins et al, 2014;Güçlü and van Gerven, 2015b, a;Wen et al, 2016Wen et al, , 2017Eickenberg et al, 2017;Seeliger et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Artificial neural networks (ANNs) are computational models that are loosely inspired by the neurosciences and are mainly composed of simple processing units and their interconnections, so ANNs can learn from experience through modifying these interconnections [25]. Various ANN models have been studied in the past and recently researched in different applications.…”
Section: Prediction Model Based On Cnnmentioning
confidence: 99%
“…127 Britain had become one of the main exporters of crops to the Rhine army, which further increased demand for produce while manpower remained the same. 128 Additionally, the church as a powerful new landowner has to be considered, negotiating land distribution, tenancy and taxation. 129 Ultimately the rural population felt the strain, as the part of society from which resources are extracted is most affected by political instability, economic change and food shortages.…”
Section: Diseases Of Deprivation?mentioning
confidence: 99%